A Five-Year Study of Cicatricial Entropion at Kirana Eye Hospital: Clinical Characteristics and Surgical Outcomes - Yunia Irawati; Bachtiar Wicaksono; Carennia Paramita (Majalah Oftalmologi Indonesia, 2021)
Purpose: Cicatricial entropion is an inward turning of eyelid margin caused by scarring tissue of the posterior lamella. The chronic damage of cicatricial entropion can irritate the ocular surface and harm the cornea. Proper reconstructive surgery techniques are needed to prevent further damage and visual impairment. This retrospective study was done to evaluate the clinical characteristics of cicatricial entropion and surgical outcomes to repair entropion at Kirana Eye Hospital, dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Methods: Records of all patients with cicatricial entropion who underwent surgical repair between January 2012 and December 2017 were reviewed retrospectively. Variables include basic and clinical characteristics, and surgical outcomes were recorded and analysed. Results: A hundred and twenty-two eyelids from 79 patients were included. Of those patients, 57% were female with mean age 51.4 years old. The laterality tendency is bilateral in 43 patients (54.4%). The most common initial complaints were foreign body sensation (35.4%). Cicatricial entropion is most commonly found on the upper eyelid (97.5%) with moderate severity. The majority of etiology is unknown but referred to chronic ocular surface inflammation in 51 eyelids (64.6%). Combined procedures were performed in most of the eyelids (79.5%). Conclusion: It is imperative that combined procedures be carried out in a moderate-severe degree cicatricial entropion. In our current study, recurrence mostly happen in patients suffering from Stevens-Johnson syndrome.